Lothal Dock hub of Maritime Trade, Transport Economics Commercial Institutions & Multimodal Transport Integration in the Indus Vally Civilization (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The National Maritime Heritage Complex can powerfully convey the story of Lothal Dock as a brilliant example of multimodal transport integration, showcasing the advanced capabilities of the Indus Valley Civilization to a global audienceLothal functioned as a thriving port city and a key economic hub of the Indus Valley Civilization, showcasing remarkable urban planning, engineering prowess, and extensive trade networks that connected it to both inland regions and far-flung ancient civilizations with multimodal maritime connectivityLothal's dock was not merely a place for ships; it was the central node where maritime voyages converged with inland river networks and overland routes, forming a seamless, efficient system for trade and commerce. This integration allowed Lothal to serve as the gateway for goods flowing into and out of the vast Indus Valley Civilization.